UTILIZING POPULATION DATA TO CHARACTERIZE NURSING HOME DECEDENTS AND THEIR FAMILIES AT THE END OF LIFE. (20th December 2022) - Stephens, Caroline; Hollingshaus, Michael; Kelly, Brenna; Tay, Djin; Ornstein, Katherine; Smith, Ken; Utz, Rebecca
Abstract: Over 2/3 of nursing home (NH) residents are eligible for palliative care (PC), but do not receive it. Utilizing the Utah Population Database, we examined EOL characteristics for 39, 672 NH residents who died in Utah between 1998-2016. Dementia was the leading cause of death (36.6%), followed by cardiovascular disease (23.9%) and COPD (16.7%). Women were more likely than men to die in a NH (21.0 vs 15%) and more likely to die in a NH with heart disease (20.0% vs. 11.7%) or cerebrovascular disease (25.9% vs. 21.0%), compared to men. Use of PC, hospice, and life-sustaining treatments was low within this NH sample, particularly among persons with dementia. First-degree family characteristics varied at EOL with presence of a spouse exerting the greatest influence on EOL care utilization. Understanding population-based NH resident EOL life characteristics can help inform the development of resident- and caregiver-centered PC interventions and health policies.